Optimization of Acetone Concentration and Reflux Ratio for Enhanced Oil Extraction from Spent Bleaching Earth: A Response Surface Methodology Approach - Monica, Clarissa Putri; Anggraeni, Verendria Putri Caesar; Sumada, Ketut; Sari, Ni Ketut; Pujiastuti, Caecilia (Indonesian Journal of Environmental Management and Sustainability, 2025)
Spent bleaching earth with an oil content exceeding 3% is classified as hazardous and toxic waste, requiring appropriate processing prior to environmental disposal. Extraction is one effective method for processing spent bleaching earth. This study focuses on the optimization of oil extraction from spent bleaching earth using acetone as a solvent, specifically analyzing the effects of solvent concentration and reflux ratio on oil recovery efficiency and evaluating the quality of recovered bleaching earth for potential reuse in vegetable oil refining processes. The extraction method employed was soxhlet extraction using acetone as the solvent. Five different acetone concentrations (50%, 60%, 70%, 80%, and 90%) were tested in combination with five reflux ratios (2, 3, 4, 5, and 6), creating a total of 25 experimental conditions. Response surface methodology (RSM) was utilized to optimize these parameters and identify the ideal conditions for maximum oil recovery. The experimental design and statistical analysis were conducted using Design Expert 13.0.5.0 software. The quality of recovered bleaching earth was assessed against Indonesian National Standards (SNI) for potential reuse applications. The optimization results indicated optimal conditions of 69.15% acetone concentration and a reflux ratio of 4, yielding a maximum oil recovery rate of 17.52%. Analysis of the recovered bleaching earth showed that while it met most SNI standards for bleaching earth quality parameters, the pH remained acidic (below neutral), indicating that alkaline pretreatment would be necessary before the material could be effectively reused in vegetable oil bleaching processes. The study demonstrates that acetone-based soxhlet extraction can effectively recover oil from spent bleaching earth while producing a secondary product suitable for reuse after appropriate pH adjustment.